Skin Necrosis with Oculomotor Nerve Palsy Due to a Hyaluronic Acid Filler Injection - Jae Il Lee; Seok Joo Kang; Hook Sun (Archives of Plastic Surgery, 2017)
Performing rhinoplasty using filler injections, which improve facial wrinkles or soft tissues, is relatively inexpensive. However, intravascular filler injections can cause severe complications, such as skin necrosis and visual loss. We describe a case of blepharoptosis and skin necrosis caused by augmentation rhinoplasty and we discuss the patient’s clinical progress. We describe the case of a 25-year-old female patient who experienced severe pain, blepharoptosis, and decreased visual acuity immediately after receiving a filler injection. Our case suggests that surgeons should be aware of nasal vascularity before performing an operation, and that they should avoid injecting fillers at a high pressure and/or in excessive amounts. Additionally, filler injections should be stopped if the patient complains of severe pain, and appropriate measures should be taken to prevent complications caused by intravascular filler injections.